2009
DOI: 10.1177/0040517509346444
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Microcapsule Adhesion to Fabrics

Abstract: IMPROVEMENT OF MICROCAPSULES ADHESION TO FABRICS ABSTRACTThe presence of microcapsules has increased in textile field. They have been applied as a possibility to introduce new products to textiles such as fragrances, antibiotic, skin hydrant, etc. This work studies the resin influence on the adhesion of microcapsules to cotton fabrics. To paste microcapsules to fabrics, they should be in contact with a bath which contains microcapsules resin and water. Different resin concentrations were applied to fragrances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 6 publications
1
35
0
3
Order By: Relevance
“…In previous studies (Monllor et al, 2010) padding procedure was tested in order to obtain the optimum conditions for the padding process. As a result conclusions showed that in order to to reach up to 20 washing cycles keeping not only microcapsules on textile surface but their active function, 60 g/L of microcapsules and 10 g/L of acrylic binder was the optimum recipe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies (Monllor et al, 2010) padding procedure was tested in order to obtain the optimum conditions for the padding process. As a result conclusions showed that in order to to reach up to 20 washing cycles keeping not only microcapsules on textile surface but their active function, 60 g/L of microcapsules and 10 g/L of acrylic binder was the optimum recipe.…”
Section: Resultsmentioning
confidence: 99%
“…All the samples were thermally dried in a scale pin stenter at 110º C for 10 min in WTC BINDER 030. Previously, it has been demonstrated that this temperature was high enough to polymerise the binder without evaporating the fragrance (Monllor et al, 2010). Table 1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples treated with an acrylic binder were cured at 110ºC. Previously, it had been demonstrated that this temperature was high enough to polymerise the binder (Monllor et al 2010). The sample treated with BTCA were cured at 160ºC, temperature necessary to achieve the crosslinking and not to change the colour of the fibre considerably (Franklin et al 1972;Socrates G 1997) …”
Section: -Preparation Of Tio 2 Fabricsmentioning
confidence: 99%
“…This process happens when a fluid flows in laminar state and breaks into droplets of a same size through an overlapped vibration. Then these drops transform into a gel in an ionic solution, resulting in the encapsulation of the active ingredient (Core) with a polymer (Shell) [27] [28].…”
Section: Introductionmentioning
confidence: 99%